Effective valorization of microalgal biomass for the production of nutritional fish-feed supplements. (10th January 2020) - Yadav, Geetanjali; Meena, Dharmendra Kumar; Sahoo, Amiya Kumar; Das, Basanta Kumar; Sen, Ramkrishna
Abstract: Falling supply and rising demand of conventional feed ingredients leads to soaring fishmeal prices, which necessitates the need for alternate feed sources. This study aims to evaluate the performance of dried dietary Chlorella sp. on the survival and growth of the freshwater juvenile- Common Carp ( Cyprinus carpio var. Koi) in a 60-day feeding trials. Microalgae was cultivated in bubble column photobioreactors with ambient air and flue gas and found to be very promising as carbon-dioxide mitigation agent. The microalgal biomass was included at dosage of 15% (w/w) to formulate two iso-nitrogenous (358 g protein kg −1 diet) and iso-caloric (19.23 MJkg −1 ) diets as a replacement of fishmeal. The algae derived diets contained essential macronutrients for the nutrition and survival of carp fishes. Performance evaluation of formulated diets vis-a-vis control feed (CF) showed significant improvement in weight gain (up to 55%), lower feed conversion ratio (2.17) and protein efficiency ratio (3.3). Cost estimates showed a marked reduction (26.10%) in cost of formulated feeds compared to conventional commercial feed that can significantly affect the profit margin of fish farmers. Further, histo-architectural changes in the intestinal sections of fishes confirmed the suitability of algal-based diets. This study highlights an interesting innovative strategy of producing cleaner microalgal biomass after waste carbon dioxide capture for the formulation of alternative nutritional feed supplement and paves a way for algal farmers to culture microalgae as unconventional feed source for the aquaculture industry. Lastly, the outcomes of this study are first of its kind in fish feed research and technology development. Graphical abstract: Image 1 Highlights: Flue gas enhanced biomass growth and CO2 fixation in Chlorella vulgaris . A nutritionally rich algae derived feed ingredient was formulated for Orange Carp. Algae-based formulated diets showed up to 55% weight gain in Carp juveniles. Histo-architectural studies suggested higher cellular activities in fishes fed with formulated feeds. Costs estimates showed a 26% reduction in feed prices of formulated feeds.